مولانا روم اور اقبال: توضیحی مطالعہ: Molana Room and Iqbal: an explanatory study - Akhtar, Noreen (Tashkeel e Jadeed, 2025)
Both Rumi and Iqbal share significant similarities. Both have built their thoughts and philosophies on Islamic teachings and love for Prophet Muhammad (peace be upon him). The core of their poetry revolves around self-realization, and they are continuous advocates of striving. According to them, worship serves not only the purpose of divine pleasure but also self-recognition. It's a pleasant truth that Rumi's ideas have endured for centuries, and as long as admirers of Rumi exist in the world, they will also delve into Iqbal's poetry.The thoughts of Allama Muhammad Iqbal and Maulana Rumi have found resonance with anyone who has contemplated them. Although there is a vast temporal gap between Rumi's era and Iqbal's, spanning many centuries, spiritually, they emerged in the same era. Their philosophies of selfhood, human love, divine love, mystical thoughts, and Islamic theories are all jewels in the same crown.